MONAZITE AGES BY THE CHEMICAL Th-U-TOTAL Pb ISOCHRON METHOD FOR PELITIC GNEISSES FROM THE EASTERN SØR RONDANE MOUNTAINS, EAST ANTARCTICA - アサミ, マサオ; スズキ, カズヒロ; アダチ, マモル; ASAMI, Masao; SUZUKI, Kazuhiro; ADACHI, Mamoru (National Institute of Polar Research, 1996)
P(論文) Chemical Th-U-total Pb isochron (CHIME) ages were determined with an electron microprobe analyzer on 14 to 24 monazite grains in three garnet-biotite gneisses collected from separate outcrops in the eastern part of the Sør Rondane Mountains, East Antarctica. On the basis of geologic and petrologic studies, investigators have inferred a two-stage metamorphic history for the Sør Rondane : (1) an earlier regional granulite-facies event inferred from U-Pb zircon and Rb-Sr and Sm-Nd whole rock data to be ∿1000Ma in age, and (2) an amphibolite-facies overprint inferred to be ∿500Ma in age. PbO-ThO_2^* plots based on ThO_2,UO_2 and PbO contents of monazites yield a well-defined isochron for each gneiss, although both matrix grains in all gneiss samples and inclusions in garnet and pyrrhotite grains in a sample were analyzed. The isochrons give 536,534 and 534 Ma ages, indicating a single crystallization age (~535Ma) for the monazites. This age is in good agreement with the ~500Ma age currently assigned to the amphibolite-facies overprint. However, the high Pb retentivity reported for monazite, along with textural and mineralogical characteristics of the samples, constrains assignment of the monazite age to the granulite-facies metamorphism rather than to retrograde recrystallization. Our ~535Ma ages give rise to a possibility of further westward extension of a Cambrian orogenic belt recently reported from the Lützow-Holm and Yamato-Belgica Complexes, where a similar succession of metamorphic and plutonic activities has been recognized. departmental bulletin paper